Classification of Adverse Events Following Surgery in Patients With Diffuse Lower-Grade Gliomas - Gómez Vecchio, Tomás; Corell, Alba; Buvarp, Dongni; Rydén, Isabelle; Smits, Anja; Jakola, Asgeir S. (Frontiers in Oncology, 2021)
BACKGROUND: Recently the Therapy-Disability-Neurology (TDN) was introduced as a multidimensional reporting system to detect adverse events in neurosurgery. The aim of this study was to compare the novel TDN score with the Landriel-Ibanez classification (LIC) grade in a large cohort of patients with diffuse lower-grade glioma (dLGG). Since TDN score lacks validation against patient-reported outcomes, we described health-related quality of life (HRQoL) change in relation to TDN scores in a subset of patients. METHODS: We screened adult patients with a surgically treated dLGG World Health Organization (WHO) grade 2 and 3 between 2010–2020. Up until 2017 it consists of a retrospective cohort (n=158). From 2017 and onwards, HRQoL was registered using EuroQoL-5-dimension, three levels of response (EQ-5D 3L) questionnaire at baseline and three months follow-up, in a prospectively recruited cohort (n=102). Both the LIC grade and TDN score were used to classify adverse events. RESULTS: In total 231 patients were included. In 110/231 (47.6%) of the surgical procedures a postoperative complication was registered. When comparing the TDN score to LIC grades, only a minor shift towards complications of higher order could be observed. EQ-5D 3L was reported for 45 patients. Patients with complications related to surgery had pre- to postoperative changes in EQ-5D 3L index values (n=27; mean 0.03, 95% CI -0.06 to 0.11) that were comparable to patients without complications (n=18; mean -0.06, 95% CI -0.21 to 0.08). In contrary, patients with new onset neurologic deficit had a deterioration in HRQoL at follow-up, with a mean change in EQ-5D 3L index value of 0.11 (n=13, 95% CI 0.0 to 0.22) compared to -0.06 (n=32, 95% CI -0.15 to 0.03) for all other patients. CONCLUSIONS: In patients with dLGG, TDN scores compared to the standard LIC tend to capture more adverse events of higher order. There was no clear relation between TDN severity and HRQoL. However, new onset neurological deficit caused impairment in HRQoL. For the TDN score to better align with patient-reported outcomes, more emphasis on neurological deficit and function should be considered.